2013
DOI: 10.1108/jrme-08-2012-0023
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between entrepreneurial marketing and the characteristics of Thai hotels and their managers

Abstract: Purpose -The purpose of this paper is to explore empirically whether there are meaningful relationships between key entrepreneurial marketing (EM) variables and the demographic characteristics of the organization and its manager. Design/methodology/approach -The data were gathered from a sample of 369 hotels from all regions of Thailand through the use of a postal survey. Several multiple regression models were used to test the relationships in the study. Interaction terms were added to some models to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Concerning the MENA countries, Bastian et al (2018) pointed out different cultural, social and organisational factors at macro/micro levels that can act as motives and challenges for women entrepreneurs. Regarding its relationship with EM, little empirical research supported that gender has an impact on EM (Boonchoo et al, 2013). Specifically, some authors contended that female entrepreneurs are more risk-averse (Malach-Pines and Schwartz, 2008;Boonchoo et al, 2013).…”
Section: Entrepreneurial Experience and Gender As Moderators For Entrepreneurial Marketing Strategy-business Performance And Institutionamentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the MENA countries, Bastian et al (2018) pointed out different cultural, social and organisational factors at macro/micro levels that can act as motives and challenges for women entrepreneurs. Regarding its relationship with EM, little empirical research supported that gender has an impact on EM (Boonchoo et al, 2013). Specifically, some authors contended that female entrepreneurs are more risk-averse (Malach-Pines and Schwartz, 2008;Boonchoo et al, 2013).…”
Section: Entrepreneurial Experience and Gender As Moderators For Entrepreneurial Marketing Strategy-business Performance And Institutionamentioning
confidence: 99%
“…Worldwide, both entrepreneurship and EM were widely being studied in SMEs of many developed countries (Franco et al, 2014;Wynn and Jones, 2019). Yet, the progression in this important research area requires more studies to be carried out on its sub-fields to examine valuable suggested relationships among its relevant variables (Boonchoo et al, 2013). Additionally, despite the successful entrepreneurial initiatives that have been detected in many emerging and Arab markets, entrepreneurship in general and EM in particular are still underresearched areas in this context (Alon and Rottig, 2013;Estrin et al, 2018) especially in Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EM synthesized into seven dimensions namely: proactiveness, calculated risk taking, innovativeness, opportunity focus, resource leveraging, customer intensity and value creation [17]. Those dimensions can be classified become two elements of entrepreneurship and marketing element [19]. Entrepreneurship element represented by pro-activeness, calculated risk taking, innovativeness, opportunity focus, and resource leveraging.…”
Section: A Entrepreneurial Marketingmentioning
confidence: 99%
“…© 2019 University of Alicante between market orientation, innovation and customer loyalty, and the business performance of Pol Clothing Group and showed that an increased degree of innovation is related to the increase in the level of market orientation. This led to an increased innovation level in company performance (M. Pakdel, Nayebzadeh, & Dehghan, 2011).According to Boonchoo et al, organization characteristics including age and size have a positive relationship with entrepreneurial marketing while the ownership and management are positively associated with market orientation (Boonchoo & Tsang, 2013). Rezvani's study showed that although the age of institute had a positive significant effect on the structure of the organization and the organization structure had a positive significant effect on the entrepreneurial marketing, institute size showed no statistically significant effect on neither the organizational structure nor entrepreneurial marketing (Rezvani, Shirkhodaie, & Khazaei, 2014).…”
Section: Introductionmentioning
confidence: 99%